Análise da multifuncionalidade da forma demonstrativa essa na perspectiva da linguística funcional clássica - Oliveira, Cláudia Sales de (2021)
This thesis analyzes the uses of the essa demonstrative form, identifying its prototypical functions and its systematicity in syntactic and semantic-discursive terms. This work belongs to the Classical Functional Linguistics (CFL) field, with a North American approach (HOPPER; THOMPSON, 1980; GIVÓN, 1984), considering the following categories: iconicity and prototypicality. It starts by defending the idea that the prototypical use of the essa pronoun comprises the following attributes: a) the adjective relationship with the accompanying noun; b) the position close to its substantive nucleus, with adjunct adjunct function; c) the syntactic-semantic relationships within the sentence in which it is inserted, contributing to a better perception of the meaning of the substantive structures with which it is related; and d) the indication, direction, with strong appeal to the locative status. Therefore, the general objective of the research is to present the multifunctionality of the essa pronominal form (and its variations), on the CFL perspective. To achieve this goal, we propose the analysis of the following criteria and parameters that guided the uses of essa form: I – Morphosyntactic functions: a) Adjective function; b) Substantive function; c) Types of DNP[SND]; II – Semantic-discursive and Pragmatic Functions: a) Nature of the name related to the DNP: concrete and abstract, b) Reference processes: Deixis: spatial deixis, temporal deixis and memorial deixis; Anaphora: Direct anaphora; associative anaphora; encapsulating anaphora; anaphora by appointment; metadiscursive anaphora; III – Structural factors: degrees of relative distance / DNP (G0, G1, G2, G3, G4). In the meantime, we present the conjunction of production contexts with parameters for analyzing the uses of essa, namely, the modality of language – oral and written, and textual genres. From the data survey of these parameters, we traced the profile of the prototypical uses of the essa demonstrative form. As for the methodological procedures, we present the quantitative and qualitative approaches to analyze 595 occurrences of the essa demonstrative form, identified in Corpus D&G/Natal (FURTADO DA CUNHA, 1998), in interviews, which took place in 5 (five) types of oral and written texts, developed equally around the following proposal: 1) narrative of personal experience; 2) narrated narrative; 3) location description; 4) procedure report; 5) report of opinion. The quantitative results indicated a predominance of the uses of essa in the adjective morphosyntactic function; in the types of DNP ESSA X and ESSA X (Z); with the concrete nature of the name in the SND and in the encapsulating and direct anaphora referencing processes. Regarding the production context, there is a predominance of uses of essa form in oral texts; in DNP, whose degree of detachment is G3 and in narrative textual genre. The more prototypical uses show the primordial function of demonstratives already mentioned, while the less prototypical uses reveal more discursive/pragmatic functions. We can conclude that the deictic and phoric primitive functions remain, both in the textual and situational perspective, revealed in the gradient scale of (+)prototypical (concrete) > (–)prototypical (abstract). However, the (–)prototypical uses also reveal that there is a regularity in the uses of the essa demonstrative form that circulate in the speeches of Portuguese users and that deserve special attention, as they reflect at the same time evidence of ongoing variation processes and uses of language in specific communicative situations for specific purposes.